Supporting interdisciplinary instruction on science, mathematics and technology for Thai gifted students: centered on Raiwa lesson plan - Chatmaneerungcharoen, S.; Sricharoen, N. (Journal of physics. Conference series, 2021)
This study focuses on teacher development through the continually action workshop of technology-enhanced integration STEM framework. The primary goal was the ambition to integrate active learning activity into national teacher training for gifted classrooms, which is provided by The Institution for the Promoting of Teaching Science and Technology—with teaching practice, aligned with professional development on teacher’s understanding of STEM activity. The study aims to identify how teachers develop their understanding of Raiwa-STEM activity, which is shown in their lesson plans. Therefore, the study focused on developing 900 in-service teachers who were science, mathematics and computer teachers that participated in this national teacher training. Data sources throughout the research project consisted of Lesson Plan Assessment, Semi-structure interviews, and document analysis. Interpretive framework was used to analyze the data. Research findings indicate that these research participants who were the teachers work closely with gifted students that have developed their understanding on the Raiwa-STEM activity. Collaboration work among teachers from different subjects encourages them to understand how the STEM activity looks like and how it transfers into an active classroom. After the teachers have experienced with Raiwa activities, they were assigned to develop their classroom implementations which were shown in their Raiwa-STEM lesson plans. From data analysis the teachers can design a connecting STEM lesson into student’s daily life, and create evaluation and assessment of the STEM classroom. The development of teachers’ understanding and practice is presented in their lesson plans that are produced during training. 75.90 % of the total STEM Lesson plans are of a good level. Moreover, the study also indicates the importance of co-working among teachers from different expertise areas in sub activities preparation that can build interdisciplinary connection of STEM concepts. Raiwa is an example of interdisciplinary instruction which can provide stud ents the use of technology-integrated knowledge and the potential of STEM-focused education to provide all students with the opportunities of STEM experience.